2016
DOI: 10.1186/s13046-016-0316-0
|View full text |Cite
|
Sign up to set email alerts
|

The clinicopathological significance of Mortalin overexpression in invasive ductal carcinoma of breast

Abstract: BackgroundMortalin/GRP75 is a ubiquitous mitochondrial chaperone which related to the cytosolic heat shock protein 70 (HSP70), and plays a role in carcinogenesis. This study aims to investigate the Mortalin expression in breast cancer and its correlation with the outcome of the patients with breast cancer.MethodsA total of 155 invasive ductal carcinoma of breast patients with strict follow-up, 52 ductal carcinoma in situ (DCIS) and 45 adjacent non-tumor breast tissues were selected for immunohistochemical (IHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
(26 reference statements)
2
30
0
Order By: Relevance
“…Moreover, the SurvExpress database showed that CRC patients with a high mortalin expression exhibited a poor OS. These observations illustrated that mortalin may play an essential role in the prognosis evaluation and treatment of CRC, which were consistent with our previous study …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, the SurvExpress database showed that CRC patients with a high mortalin expression exhibited a poor OS. These observations illustrated that mortalin may play an essential role in the prognosis evaluation and treatment of CRC, which were consistent with our previous study …”
Section: Discussionsupporting
confidence: 93%
“…These observations illustrated that mortalin may play an essential role in the prognosis evaluation and treatment of CRC, which were consistent with our previous study. 26 Previous studies have emphasized that mortalin participated in tumorigenesis and tumor progression. The suppression of mortalin expression may contribute to TP53 activation and apoptosis induction in del(5q)-associated myelodysplastic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Also recent data agreed with study made by Salda and Romanucci,(2012) they observed correlation among members of small HSP, HSP70 and HSP90 families have been studied extensively in (BC) with ER,PR and HER-2.and suggested with by Jin et al,(2016) they reported HSP70 is upregulated in (BC), and may be a useful poor prognostic biomarker as well as a potential therapeutic target for patients with(BC). Small HSP, HSP70 and HSP90 families are involved in the regulation of estrogen receptors (ER) and hence have been extensively studied in human (BC) where they play a role in tumor cell proliferation, differentiation, invasion, metastasis, cell death and tumor immune response (Conroy and Latchman,1996;Ciocca and Calderwood,(2005 Further multivariate survival analysis showed that HSP70 expression was one of the independent prognostic factors, along with clinical stage and Her2 status (Dundas,etal.,2005;Jin, et al2016 ).…”
Section: -Correlation Of (Hsp70) With (Erprher2) Receptorssupporting
confidence: 78%
“…GRP75 is positely involved in the carcinogenetic process, due to its ability to prevent the transcriptional activation and the pro-apoptotic functions of the p53. It has been documented that its over-expression correlates with the increase of breast carcinoma cell malignancy and with poor prognosis for breast cancer patients [151,152]. In our tumor tissues, when present, it reached rather high expression values (5,4x).…”
Section: Grp75 (Hspa9)mentioning
confidence: 77%